Preparing future teachers to evaluate learning outcomes - Tuna, Salih; Boranbayeva, Aktolkyn; Gani Isaev, Baktiyar Ortayev, Abdinabi Isaev,; Mussabekova, Gulnar (Opción, 2019)
Education is important for the implementation of socio-economic development of the country. Therefore, it is known that the conformity with the needs of society to assess the quality of education, technology and teaching methods, implementation of social and professional mobility of a modern specialist who is able to improve their knowledge are reflected in educational programs and concepts. The theme of the Address of the nationwide leader Nursultan Nazarbayev in 2012 - “Socio-economic modernization is the main vector of development of Kazakhstan” is obvious to the people, including teachers.It is known that the address has a distinctive feature for teachers. The President paid particular attention to human capital, among the priority areas, saying that qualitative growth of human capital in Kazakhstan, is primarily related, in particular to education and healthcare, "Firstly, introduction of modern methods and technologies into the learning process; Secondly, it is important to improve the quality of teachers;...fifthly, learning should not only provide education to youth, but also teach how to use education in the process of social adaptation; sixthly, it is necessary to strengthen the educational component of the educational process"- noted he the importance of measures.These issues promote the organization of the educational process, which is the basis of the knowledge acquisition, and the quality of training of future teachers. Evaluation of educational achievements, learning outcomes of schoolchildren was considered as a component of pedagogical, methodological training of the teacher. At the same time, it is necessary to study the readiness of teachers to assess. The article outlines the model for preparing future teachers to assess the learning outcomes, which has been experimentally tested. The aim of the research is to determine the level of readiness of future elementary school teachers to evaluate the outcomes of their learning/teaching via comparative qualitative research methods. As a result, the readiness of future teachers to evaluate student performance in the established and non-established state of education are not well studied. In conclusion, If the training of future teachers is carried out in accordance with the readiness to evaluate learning outcomes, this will prepare future teachers for developing and implementing learning outcomes/teaching outcomes of students and their evaluation criteria.